TANGGUNGJAWAB PARA PIHAK YANG MELAKUKAN WANPRESTASI DALAM PERJANJIAN USAHA WARALABA ONLINE - Erniwati Erniwati; Hj. Suryani Yusi (Justici, 2021)
The franchise agreement is a legal guide that outlines the responsibilities of the franchisor (often called the franchisor) and the franchisee (which is often called the franchisee). When the franchisee agrees to the franchise business offered to him, he must comply with the existing agreement. the same should also apply to online franchises. On average, these online franchises are small-scale franchises, if anyone is interested in running this business, the agreement or agreement occurs only through social media without a standard agreement between the two parties. They did not see each other nor did they have any job training related to marketing concepts. When the agreement exists and a certain amount of money has been sent, that's when the online franchise agreement took place. The responsibilities of the parties in the online franchise agreement are contained in Articles 5, and 7 of Law Number 8 of 1999 concerning Consumer Protection.